(untitled) (Journal of the College of Basic Education, 2022)
The topic of sentence breaks has received great attention from scholars and researchers, especially the Qur’anic commas, while the research and studies that have been concerned with the Noble Prophetic hadith are almost few. The descriptive analysis approach, and its application to a selected sample of the hadiths, and one of the most important results of the research: that one of the types of commas that were used in the noble hadith is the symmetrical, parallel, extreme, and balanced comma. And that most of the morphological formulas for commas in the honorable Prophetic hadith are exaggerated forms, which bear many connotations, such as urging to do something or forbidding it, warning, enticement, intimidation, lack and abundance in the plural, and other indications that are associated with forms of exaggeration, and differ according to the different words. The researcher recommended carrying out a set of relevant research and studies .